Developing Digital Flipbook-Based English Writing Materials for EFL Vocational High School Students - Waluyo, Waluyo; Sihite, Meida Rabia; Fransiska, Widia (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
English writing skills are pivotal for vocational students and their future careers. To improve students' writing skills, technology development provides access for teachers to create digital learning resources. Moreover, the Ministry of Education, Culture, Research, and Technology requires teachers to integrate technology in the classroom. However, preliminary research found that the teacher was not using technological-based learning resources. Therefore, the objectives of this study were to identify the needs of twelfth-grade students of vocational schools and to develop digital flipbook-based English writing materials. This study used a Research and Development (R&D) approach, with participants being twelfth-grade students from SMK Negeri 5 Medan. The research procedures followed ADDIE (Analysis, Design, Develop, Implementation, Evaluation). Instruments included needs analysis, expert judgement, teacher’s review, and students’ response questionnaires. The data were analyzed quantitatively and qualitatively. The results of needs analysis indicated that most of the students wanted to improve their grammatical accuracy in their writing, After developing the product, the final overall score obtained from the expert, teacher and students was 3.67, categorizing the materials as